Pengaruh Rasio Jambu Merah Dan Santan Kelapa Terhadap Mutu Kimia Dan Mutu Fisik Mellorine Jambu Biji Merah - Wafa’ Amatul Azizah; Mazarana Devi; Issutarti Issutarti (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2023)
Mellorine is one of various types of ice cream, but has a composition that is not the same as ice cream in general. The difference between mellorine and ice cream lies in the use of fat. Ice cream uses milk fat, while mellorine uses vegetable fat. One of the fats that can be used is coconut milk. The manufacture of mellorine utilizes the abundant production of red guava fruit, in addition to adding to the taste of red guava it is also expected to increase the nutritional value of mellorine. The purpose of this study was to examine the chemical properties, namely fat content, Vitamin C, dietary fiber, and pH and physical properties, namely overrun, and melting speed. The results showed that the fat content showed a significant difference which ranged from 3.49%-5.9%, the Vitamin C content ranged from 36.67mg/100g-48.67mg/100g, while the dietary fiber content ranged from 12.75%. -15.54%, and pH did not show any difference. The results of the physical test showed that there was a significant difference in the overrun, which ranged from 52%-71.5%, and the melting speed ranged from 54.5 minutes to 63 minutes.